Interspecific variations in the gastrointestinal microbiota in penguins. Issue 1 (25th January 2013) - Dewar, Meagan L.; Arnould, John P. Y.; Dann, Peter; Trathan, Phil; Groscolas, Rene; Smith, Stuart
Abstract Despite the enormous amount of data available on the importance of the gastrointestinal (GI) microbiota in vertebrate (especially mammals), information on the GI microbiota of seabirds remains incomplete. As with many seabirds, penguins have a unique digestive physiology that enables them to store large reserves of adipose tissue, protein, and lipids. This study used quantitative real‐time polymerase chain reaction (qPCR) and 16S rRNA gene pyrosequencing to characterize the interspecific variations of the GI microbiota of four penguin species: the king, gentoo, macaroni, and little penguin. The qPCR results indicated that there were significant differences in the abundance of the major phyla Firmicutes, Bacteroides, Actinobacteria, and Proteobacteria. A total of 132, 340, 18, 336, 6324, and 4826 near full‐length 16S rRNA gene sequences were amplified from fecal samples collected from king, gentoo, macaroni, and little penguins, respectively. A total of 13 phyla were identified with Firmicutes, Bacteroidetes, Proteobacteria, and Fusobacteria dominating the composition; however, there were major differences in the relative abundance of the phyla. In addition, this study documented the presence of known human pathogens, such as Campylobacter, Helicobacter, Prevotella, Veillonella, Erysipelotrichaceae, Neisseria, and Mycoplasma. However, their role in disease in penguins remains unknown. To our knowledge, this is the first study to provide an in‐depth investigation of the GI microbiota of penguins.